An introduction to vascular biology : from basic science to clinical practice - Hunt, Beverley J. (Cambridge University Press, 2002)
Vascular biology is an exciting and rapidly advancing area of medical research, with many new and emerging pathophysiological links to an increasing number of diseases. This updated and expanded new edition takes full account of these developments and conveys the basic science underlying a wide range of clinical conditions including atherosclerosis, hypertension, diabetes, and pregnancy. As with the first edition, the publication provides an introductory account of vascular biology before leading on to explain mechanisms involved in disease processes. Other emerging topics include the role of nitric oxide and apoptosis in vascular biology. The breadth and range of subjects covered in this new edition do full justice to this increasingly important area of clinical research and medicine. This multidisciplinary approach will suit the needs of all those seeking to refresh their knowledge with the very latest advances from basic science through to clinical practice.